Correlation between Self-compassion and Academic Procrastination with Learning Achievement among the Medical Students at Universitas Swadaya Gunung Jati, Cirebon, Indonesia - Septiawati, Ayu Dwi; Sulistiyana, Catur Setiya; Primanagara, Risnandya (GHMJ (Global Health Management Journal), 2024)
Background: Learning achievement is primarily measured by GPA. A positive self-concept, nurtured by self-compassion, is essential for achieving academic excellence. Self-compassion helps students cope with stress and boost motivation. On the other hand, procrastination is a common obstacle to academic success. Ineffective time management and organizational skills are hallmarks of procrastination. Aims: To describe the levels of self-compassion and procrastination among medical students and to examine how these factors relate to academic performance. Methods: This study employed a cross-sectional design involving 266 active medical students at UGJ, selected through stratified random sampling. Data was collected using an online questionnaire, including the Self-Compassion Scale and the Academic Procrastination Scale. Univariate and bivariate analyses were conducted, with a Spearman correlation test used to assess the correlation between variables due to the non-normal distribution of self-compassion and academic achievement. Results: The majority of participants exhibited moderate levels of self-compassion (56%). Similarly, the majority (38.7%) demonstrated moderate levels of academic procrastination. In terms of learning achievement, the majority of participants achieved a GPA between 3.01 and 3.50 (32.3%). A significant positive correlation was found between self-compassion and learning achievement (p-value<0.001, r=0.339). Conversely, a significant negative correlation was observed between academic procrastination and learning achievement (p-value<0.001, r=-0.234). Conclusion: This research shows that higher self-compassion is associated with better learning outcomes whereas higher academic procrastination is associated with worse learning outcomes.   Received: 25 September 2024  |  Reviewed: 17 October 2024  |  Revised: 17 November 2024  |  Accepted: 30 November 2024.